2011
DOI: 10.1021/ml200108y
|View full text |Cite
|
Sign up to set email alerts
|

Monoenomycin: A Simplified Trienomycin A Analogue That Manifests Anticancer Activity

Abstract: Macrocyclic natural products are a powerful class of lead-like chemical entities. Despite commonly violating Lipinski’s “rule of 5”, these compounds often demonstrate superior drug-like physicochemical and pharmacokinetic attributes when compared to their acyclic counterparts. However, the elaborate structural architectures of such molecules require rigorous synthetic investigation that complicates analogue development and their application to drug discovery programs. To circumvent these limitations, a conform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 21 publications
1
12
0
Order By: Relevance
“…66 After generating low-energy conformations of the semi-synthetic analogues with SYBYL, 67 Blagg and co-workers showed that while Funayama’s inactive derivatives exhibited significant conformational differences from trienomycin A, the active methyl ether analogue retained the parent geometry. The Blagg group hypothesized that mimicking the conformational preferences of 21 properly orients the critical phenol unit and N -acylated side chain within trienomycin’s binding pocket, thereby promoting tight binding.…”
Section: 1 Conformational Mimics Of Polyketide Natural Productsmentioning
confidence: 99%
“…66 After generating low-energy conformations of the semi-synthetic analogues with SYBYL, 67 Blagg and co-workers showed that while Funayama’s inactive derivatives exhibited significant conformational differences from trienomycin A, the active methyl ether analogue retained the parent geometry. The Blagg group hypothesized that mimicking the conformational preferences of 21 properly orients the critical phenol unit and N -acylated side chain within trienomycin’s binding pocket, thereby promoting tight binding.…”
Section: 1 Conformational Mimics Of Polyketide Natural Productsmentioning
confidence: 99%
“…Successful Weinreb amidation of several Boc-amino acids (63-97% yield) and aliphatic acids has been recently achieved [15,33]. In addition, the use of COMU (16) in bioconjugation, anilide, and PNA-based construct formation has been described in numerous occasions [27,[34][35][36][37][38][39].…”
Section: Biographiesmentioning
confidence: 99%
“…Two upregulated DAPs identified as transketolase were enriched in the “biosynthesis of ansamycins” pathway, suggesting that these bacterial macrocyclic polyketides with demonstrated antimicrobial ( 62 ), anticancer ( 63 ), and antiviral ( 64 ) activities could be playing important roles in Btk’s survival in the hemolymph. The only known ansamycins of Bacillus origin are the antibiotic aurantinin and antivirals hydroxymycotrienins A and B ( 65 , 66 ).…”
Section: Discussionmentioning
confidence: 99%